Analysis of Factors Influencing the Shift in Payment Methods for Ride-Hailing Services - Bella Nathaya Chantika; Adnan Kasofi; Fildzah Shabrina (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study analyzes the effects of perceived transaction cost, dissatisfaction, perceived ease of use, perceived value, and inertia on users' switching intention to shift from OVO to QRIS as a payment method in Grab ride-hailing services. Grounded in the Push–Pull–Mooring (PPM) framework, the study adopts a quantitative approach by administering an online questionnaire to 200 Generation Z and young Millennial respondents aged 18–35 years in the Greater Jakarta area (Jabodetabek) who had experience using OVO and were familiar with the QRIS payment feature on the Grab application. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The measurement model confirmed that all constructs achieved the required validity and reliability criteria. The structural model indicated that dissatisfaction, perceived ease of use, and perceived value had significant positive effects on switching intention, whereas perceived transaction cost and inertia were not found to have significant effects. These findings suggest that users' intention to switch to QRIS is primarily driven by dissatisfaction with the existing payment method and by the perceived convenience and value offered by QRIS. The study provides practical insights for Grab and digital payment providers in formulating strategies to accelerate the adoption of interoperable digital payment systems.